2020
DOI: 10.14710/ijred.2021.33485
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Module Degradation on the Viability of On-Grid Photovoltaic Systems in Mediterranean Climate: The Case of Shymkent Airport

Abstract: This paper presents the techno-economic feasibility analysis of an on-grid Photovoltaic Solar System (PVSS) subject to Mediterranean climate aging effects. The PVSS under study is considered installed on the roof of Shymkent airport, located in southern Kazakhstan. A PVSS performance degradation rate of 1.48%-per-annun was considered according to the Mediterranean climate prevailing in the location. A 25-year life-cycle cost analysis comparing the rated vs. de-rated on-grid PVSS led to a positive Net Present V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The most complete assessment of the relationship between degradation processes and the variability of the energy performance of buildings is possible only with a simultaneous assessment of the economic benefits. For example, Smagulov et al [32] conducted the techno-economic feasibility analysis of an on-grid photovoltaic solar system installed on the roof of an airport, taking into account its degradation, and found that a possible reduction in key financial indicators might range from 16.2 to 43.5% over 25 years.…”
Section: Existing Approaches To Assessing the Deterioration Of Buildi...mentioning
confidence: 99%
“…The most complete assessment of the relationship between degradation processes and the variability of the energy performance of buildings is possible only with a simultaneous assessment of the economic benefits. For example, Smagulov et al [32] conducted the techno-economic feasibility analysis of an on-grid photovoltaic solar system installed on the roof of an airport, taking into account its degradation, and found that a possible reduction in key financial indicators might range from 16.2 to 43.5% over 25 years.…”
Section: Existing Approaches To Assessing the Deterioration Of Buildi...mentioning
confidence: 99%